Favelas ecológicas: passado, presente e futuro da favela turística - Moraes, Camila Maria dos Santos (2017)
Favelas of Rio de Janeiro have been historically elaborated as deforestation, risk areas, poverty and violence, problems that affect 'the marvellous city'. Through history therefore, these were the meanings imposed to favelas by public policies. However, and against all odds, selected favelas were discovered by tourists, just before the Earth Summit - Eco 92, the United Nations Conference on Environment and Development, based in Rio. Between 1990 and 2000, these favelas consolidated as tourist attractions competing with Corcovado and Sugar loaf. The controversial visits were accused of being 'poverty safaris' or 'poverty zoos'. In the 2000s, the State recognized these areas as tourist attractions and stimulated the commercialization of favelas in the context of megaevents, which came with urbanization policies such as the Growth Acceleration Program (PAC) and Carioca Living (Morar Carioca), and a new public security policy the Pacifying Police Units (UPP). The social version of these projects has put tourism on the agenda. Consultants, analysts and technicians were hired to carry out studies of potentialities and capacities of favela residents to undertake tourism business which expanded and crossed the borders of the southern zone, reaching the centre, north and west of the city, in smaller proportions. While it spread, this tourism specialized and differentiated itself. Tourists could find the most diverse experiences in favelas, from the local gastronomy, museums, art gallery, to luxurious lodgings, parties and funk dances, that gathered cariocas and tourists in expensive spaces inside favelas. This expansion / transformation came to be perceived as a problem. The increase of economic value inside favelas areas began to reach those who could no longer remain in these places. The most diverse movements of resistance appeared, from those that go against the tourism in favelas, to those who want to be part, but in its way. In this context, I have found proposals for community-based tourism that have gained strength in local discourse as an alternative to mass tourism, and ecotourism proposals, combining elements of community-based tourism with preservation of the environment. Thus, with the theoretical framework of the New Mobility Paradigm (Sheller and Urry, 2006, 2016) and the phenomenon of the traveling favela (Freire-Medeiros, 2013), I analysed community-based tourism and ecotourism initiatives, seeking to understand their origins and proposals of an alliance between tourism and the environment. For that, I performed a multisited ethnography, where I moved through the expansion of tourism in Rio de Janeiro favelas in the context of megaevents. Throughout the research, I noticed that tourism and the networks it mobilizes have put in dispute new meanings for the favelas, and in the specific case of this thesis, the anti-ecological favela contestation. Thus, I present the various speeches of State, consultants, analysts and local entrepreneurs who mobilized for or by the expansion of tourism in favelas reflected on the past, present and future of favelas.